PENGARUH CAPITAL ADEQUACY RATIO, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL DAN LOANS TO DEPOSIT RATIO TERHADAP RETURN SAHAM INDUSTRI PERBANKAN - L, Al Azhar (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
The research was conducted in order to find out empirically the influence of theCAR, BOPO and LDR on the banking industry stock returns in IDX. METHODsampling done by purposive sampling, and acquired 20 banking companiesregistered in IDX observations in 2006-2008. Financial report form data obtainedfrom the Indonesian Capital Market Directory. And data analysis methods used forhypothesis testing is multiple linear regression. Results of this study show that: CARand LDR no significant effect on stock returns, while BOPO significant effect on thebanking industry stock returns in IDX. Coefficient of determination (R2) variableCAR, BOPO and LDR is as big as 39.6% in explaining the variation in stock returnsin the banking industry IDX.Keywords: stock return, CAR, BOPO, and LDR